Effects of Service Quality on Word of Mouth through Satisfaction in Outpatient at Sakinah Islamic Hospital in Mojokerto Regency - Nurul Agustin; Sri Hernawati; Sebastiana Viphindrartin (Health Notions, 2018)
Hospital is health service institution organizing individual health service. In an increasingly competitive environment, hospitals should be increasingly aware of the importance of providing the best quality service for the patients. In Sakinah Islamic Hospital showed the decrease of the number of outpatient patient visits, on 2014 until 2016, decreasing by 697 patients. This research aimed to analyze the effects of service quality on word of mouth through patient satisfaction. This was quantitative research with observational analytic approach. The samples of this research were 90 outpatients using multistage sampling technique. The data analysis was conducted by using Partial Least Square. Based on the testing result, it was found the effects of service quality on word of mouth through satisfaction, with t-statistic value by 2.039 (t-statistic > t table of 1.96). It means that the better service quality provided, the higher the level of patient satisfaction and increase the word of mouth as well. Sakinah Islamic Hospital needs to improve the quality and quantity of the human resources, equip facilities infrastructure and conduct maintenance and repair to support the service continuity for the patients, therefore, they will be satisfied and encouraged to do word of mouth and increase the number of patient visits. Keywords: Service quality, Satisfaction, Word of mouth.